Trust Management in Organic Agriculture: Sustainable Consumption Behavior, Environmentally Conscious Purchase Intention, and Healthy Food Choices - George Lazaroiu; Mihai Andronie; Cristian Uţă; Iulian Hurloiu (Frontiers Media S.A., 2019)
We draw on outstanding recent research to substantiate factors driving pro-environmental food purchasing behavior. Throwing light on purchasing behavior for environmentally sustainable foods, our study highlights the relevance of consumer trust and motivations in organic product markets together with individuals' perceived value and willingness to buy such items throughout the choice behavior and decision-making process. Our findings prove that most aspects influencing consumers' attitudes for and choices of organic foods are related to their trust and perceptions of the nutritional benefits such products provide. The insights gained from our research extend present knowledge concerning consumer behavior and purchase intention for environmentally sustainable products. The chief gaps and issues identified by the review cover the variety of organic food consumer purchase intentions and behaviors, including the relative environmental performance of organic food production and the link between the motivational values and attitudes concerning the consumption of non-chemical products. Apart from sustainable agriculture and upsides of organic farming, the main disadvantages are as follows: recycling and aligning with natural operations does not necessitate chemical inputs, but organic food is more prohibitive as farmers do not obtain significant crop productivity out of their land, while organic goods may have a price of up to 40% more (production expenses are steeper because farmers demand more labor force), marketing and distribution are not streamlined as organic products are delivered in diminished volumes, food disorders may occur more frequent, and chemical-free agriculture cannot produce sufficient nutrients that the world's population requires to live on.